The Semiotics Analysis of The Movie Poster "Ipar Adalah Maut" - Tiara Nurwanti; Zaenul Wafa (Journalistics: Journal of English Teaching and Applied Linguistics, 2024)
This study seeks to critically examine the semiortic elements embedded within the promotional poster for Indonesian Ipar adalah Maut. A poster plays a crucial role in the marketing strategies for cinematic productions, serving as visual medium that comprises the essence of the film. Ipar adalah Maut, a roumantic drama produced by MD Pictures and Manoj Punjadi, and directed by Hanung Bramantyo, serves as the focal point of this study. A qualitative analysis methodology was employed to explore the selected Movie Poster, utilizing Saussure’s semiotic theory as the primary analytical framework. This approach is further enriched by including Darmaprawita’s color theory and Barthers’ concepts of the relationship between the signifier and the signified, as well as the process through signing generate connotative and denotative meaning. The findings of this research reveal that the poster’s illutions of the main characters, accompanied by various props, convey critical information about the narrative themes and storylines presented in the movie. These visual elements function not merely as decorative features but as integral components of the poster’s overall semiotic structure, contributing to the audience’s understanding and interpretation of the film’s content. Through this analysis, the study hightights the intricate interplay between visual design and meaning-making in Movie Posters, underscoring their significance in shaping audience expections and perceptions.